Harnessing the Potential for Green Growth in Kuwait - Al-Ahmad, Mohammed; Dimashki, Marwan; Al-Duaij, Samia; Roundell, Tom (World Bank, Washington, DC, 2014)
Like many countries in the Middle East and North Africa (MENA) region, Kuwait faces considerable environmental challenges due to air pollution, increasingly scarce water resources and deteriorating arable land. As the problems associated with climate change intensify, governments and countries need to respond with more creative and wide ranging policy responses in order to safeguard the standards of living for future generations. While the challenges faced by countries like Kuwait are formidable, they also present an exciting opportunity for diversifying an oil based economy through green growth initiatives. Part of the motivation behind the World Bank's cost of environmental degradation report prepared in partnership between the World Bank and the Environment Public Authority (EPA) in Kuwait is to highlight the path to efficient resource allocation by properly costing the externalities that affect the economy. By using the tools of economics to analyze the impacts of environmental degradation and climate change, the report hopes to highlight the positive incentives for good environmental practices, and in particular illustrate how difficult challenges present opportunities to diversify the economy through green growth, and generate sustainable jobs and income for future generations. A good chance for investment in green economy in Kuwait also exists in introducing improvements in the solid waste segregation, collection and disposal practices, and better recycling mechanisms for the recovery of valuable materials. Allowing fish stocks to recover in Kuwait will revive the flagging fishing industry, generate tourism revenues, and help Kuwait rediscover its fishing heritage.